Nostalgia as a repository of social connectedness the role of attachment-related avoidance.[article]. - Wildschut, TIm
Individuals who are low (compared with high) in attachment-related avoidance rely on social bonds to regulate distress, and the authors hypothesized that nostalgia can be a repository of such social connectedness. Studies 1-3 showed a positive association between loneliness and nostalgia when attachment-related avoidance was low, but not when it was high. Study 4 revealed that low-avoidance individuals derived more social connectedness from nostalgia than did high-avoidance individuals. Study 5 extended these findings and demonstrated that, in addition to being a source of social connectedness, nostalgia increased participants' perceived capacity to provide emotional support to others. As in the case of social connectedness, this beneficial affect of nostalgia was significantly stronger when attachment-related avoidance was low (compared with high). -- (from the author)
Keywords: Nostalgia; Attachment; Loneliness; Social connectedness